Business of Local Fruit and Vegetables in Jember District as a Support of Food Security, Indonesia - Sawitri Komarayanti; Wiwik Suharso; Elfien Herrianto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Local fruits and vegetables contribute to food security in the area. Efforts to gather information about local fruits and vegetables is very important. This is due to the diversity of local fruit and vegetables are endangered due to the penetration of imported fruits and vegetables that increasingly dominate, changing consumption patterns and land use. This study examines the diversity of local fruits and vegetables in Jember. The research method using exploratory survey which aims to gather information with a qualitative approach. The research instrument is observation sheet, interview and documentation. The survey area covers 31 districts in Jember, namely:Subdistrict Kencong, Gumukmas, Puger, Wuluhan, Ambulu, Tempurejo, Silo, Mayang, Mumbulsari, Jenggawah, Ajung, Rambipuji, Balung, Umbulsari, Semboro, Jombang, Sumberbaru, Embankment, Bangsalsari, Panti, Sukorambi, Arjasa, Pakusari, Kalisat, Ledokombo, Sumberjambe, Sukowono, Jelbuk, Kaliwates, Sumbersari and Patrang, Respondents were interviewed are traders of fruit and vegetables in the market and the centers of the fruit. The results of this exploratory study found that 46 kinds of local fruits and 52 kinds of local vegetables. 52.2% met the local fruit is cultivated, ie 24 types of local fruits such as:Avocado, Grapes, Belimbing, Duku, Durian, Guava, Guava Water, Orange Semboro, Orange Large, longan, mango, mangosteen, Melinjo, jackfruit, pineapple, papaya, banana, rambutan, Salak, Sawo, passionfruit, soursop and breadfruit. 30.8% of local vegetables that have been cultivated at 16 types of local vegetables such as: Bawang Merah, Bawang leaves Cabbage, Cauliflower, chinese cabbage / mustard, Long Bean, Large Chilli, chilli, Mushroom, Tomato, eggplant, beans, cucumber, pumpkin Siam, Kale and Spinach,